A comparison of neurokinin 1 receptor knock-out (NK1−/−) and wildtype mice: exploratory behaviour and extracellular noradrenaline concentration in the cerebral cortex of anaesthetised subjects - Herpfer, Inga; Hunt, Stephen P.; Stanford, S. Clare (Neuropharmacology, 2005)
In behavioural screens, mice lacking functional NK1 receptors (NK1−/−) resemble wildtypes (NK1+/+) that have been given an antianxiety/antidepressant drug. Most, if not all, antidepressants increase noradrenergic transmission in the brain. Here, we have used in vivo microdialysis to compare the concentrations of extracellular noradrenaline (‘efflux’) in the cerebral cortex of anaesthetised NK1−/− and NK1+/+ mice. The effects of systemic administration of the antidepressant, desipramine, with and without local infusion of the α 2-adrenoceptor antagonist, RX821002, were also evaluated. Finally, we compared the effects of desipramine on behaviour of NK1+/+ and NK1−/− mice in an activity chamber and in a light/dark exploration box. Basal noradrenaline efflux was increased 2 to 4-fold in NK1−/− mice compared with NK1+/+ mice but there was no difference in the effects of desipramine. RX821002 increased noradrenaline efflux in all vehicle-injected mice but, in desipramine-pretreated mice, noradrenaline efflux was increased in NK1+/+ mice, only. All behaviours in the light/dark exploration box differed in the two genotypes. Furthermore, with the exception of ‘grooming’, the effects of desipramine on behaviour of NK1−/− mice could be explained by the effects of this antidepressant on locomotor activity. Finally, α 2-adrenoceptors are possibly desensitised in NK1−/− mice. We have yet to establish whether this is a cause or a consequence of the increased noradrenaline efflux.